Through my eyes - Tebow, Tim, 1987-; Whitaker, Nathan (New York : HarperCollins, 2011)
One of the best quarterbacks in the history of college football traces his path to success, discussing his childhood as the son of Christian missionaries and how his faith combined with his drive to succeed have made him the person he is today.
Keywords: Tebow, Tim, -- 1987-; Football players -- United States -- Biography